Comparison of clinical significance between optical coherence tomography guided percutaneous coronary intervention and angiography-guided percutaneous coronary intervention in acute coronary syndrome of the south zone of Tamil Nadu - Narayanan G,; Ravichandran Edwin JM,; Antoprabhu R,; Manikandan S, (Asian Journal of Medical Sciences, 2023)
Background: Intravascular optical coherence tomography (OCT) has specific features favoring its utilization in acute coronary syndrome (ACS). OCT has 100% sensitivity for detecting intraluminal thrombus compared to conventional coronary angiograms. Aims and Objectives: This study compares the clinical significance of OCT findings during percutaneous coronary intervention (PCI) and angiography-guided PCI in ACS patients. Materials and Methods: This prospective observational study was conducted in a tertiary care cardiac center at Tirunelveli Medical College Hospital and included 43 patients who had undergone both conventional and OCT-guided stenting (PCI) coronary angiograms. Their pre- and post-stenting findings of Intravascular OCT, conventional angiogram findings, and follow-up coronary angiogram findings were recorded. Results: The mean age of the patients was 51.61 years, with 20 (87%) males and 19 (86.4%) males in the OCT-guided PCI group. Baseline risk factors such as hypertension, smoking, and T2DM were noted. Pre-OCT showed fibrofatty plaque, plaque rupture, red thrombus, spotty calcium, mixed thrombus, and white thrombus. Post-stenting OCT results showed 13.6% Edge dissection, 9.1% Malapposition, 9.1% Red thrombus, 4.5% Tissue prolapse, and 4.5% white thrombus. Five patients had chest pain on follow-up; a check angiogram showed stent thrombosis and restenosis in four cases (17.4%), and reintervention was done. One case of early stent thrombosis expired, which is statistically significant. Conclusion: Intravascular OCT is a promising new and advanced technology for intra-coronary imaging due to its high resolution and dynamic range.